Causes of hospitalization and predictors of in-hospital mortality among people living with HIV in Sicily-Italy between 2010 and 2021 - Luca Pipitò; Giuseppe Zinna; Marcello Trizzino; Claudia Gioè; Manlio Tolomeo; Paola Di Carlo; Claudia Colomba; Lidia Gibaldi; Chiara Iaria; Piero Almasio; Antonio Cascio (Elsevier, 2023)
Background: Despite the rising number of people living with human immunodeficiency virus (HIV), there is a lack of knowledge about the factors that lead to PLWHs being hospitalized in worldwide literature. Our study aimed to investigate PLWH admissions in Sicily (Italy) between January 2010 and September 2021 and to analyze the characteristics and risk factors for in-hospital mortality and differences between Italians and foreigners. Methods: Data from the hospital discharge forms of all people living with HIV (PLWH) hospitalized in Sicilian hospitals were retrospectively collected. Age, sex, nationality, length of stay, acquired immunodeficiency syndrome (AIDS), and non-AIDS-related diseases were evaluated using univariate analysis according to in-hospital mortality rates. The factors associated with mortality were included in the logistic regression model. Results: In total, 5281 admissions from 2726 PLWHs occurred, most of which were related to non-AIDS diseases. Approximately 20 % regarded foreign patients, mainly from Africa. Logistic regression analysis revealed an association between in-hospital mortality and some AIDS- and non-AIDS-related diseases (wasting syndrome, lymphomas, Kaposi sarcomas, progressive multifocal leukoencephalopathy, cryptococcosis, abscesses, sepsis, cardiovascular disease, nephropathy, and respiratory diseases). African patient admissions were significantly associated with tuberculosis, toxoplasmosis, Burkitt lymphoma, and hepatitis B diagnoses. Conclusions: Our study showed that most hospitalizations were related to non-AIDS-defining diseases, with differences between Italian and foreign patients, mainly from Africa.